The Prevention of Crime (Amendment and Extension) ACT 2013: a comparison with the Criminal Law (Temporary Provision) (Amendment) ACT 2013 of Singapore / Nadrah Jamil … [et al.] - Jamil, Nadrah; Mohd Hussin, Nur Haffida; Mohammad Nawawi, Nurfatihah; Sulaiman, Siti Shawarti (2014)
The main concern of this research is to make a comparison on the new amended law in Malaysia which is the Prevention of Crime (Amendment and Extension) Act 2013 (POCA) with Criminal Law (Temporary Provision) (Amendment) Act 2013 (CLTPA) on the effectiveness of the act pertaining to the criminal offences. The comparative issues will cover on 3 aspects where the first issue is the amended law excludes the provision of judicial review. Secondly on the issue of POCA 2013 denying the right to legal representation and perceived by many as being violation to the justice system in Malaysia and lastly on the issue of the incomprehensiveness of the law to stop any future abuse of power. Discussion is also made on the development of the preventive detention legislation in Malaysia and Singapore is being referred to as a model in this aspect.